WACANA EKSPRESI HUMOR DAN KREATIVITAS MEME FILM PENGABDI SETAN 2017 - Pramesti Saniscara; Elda Franzia Jasjfi; Agung Eko Budi Waspada (Universitas Trisakti, 2021)
AbstractDigital Democracy in Popular Culture: Meme and Political Critics. Meme has become a popular subculture that cannot be separated from the internet sphere. Meme have become an agent of free speech that allows a discourse to be communicated, modified, disseminated without the need of conventional conversation. The upcoming Presidential Election 2019 in Indonesia has become one of the discourses that often, using memes as its agent. Memes, while being a medium of expressed humor and satire, also become a media critic of Indonesian democracy practices. This journal sees the meme of Nurhadi-Aldo as a discourse of political criticism wrapped in comedy and satire in response to the 2019 Presidential Election using structuralism approach from Anthony Giddens.Keywords: Internet, memes, Abstrak Wacana Ekspresi Humor Dan Kreativitas Meme Film Pengabdi Setan 2017. Meme sudah menjadi subkultur populer yang tidak bisa dipisahkan dari dunia internet. meme sudah menjadi sebuh media ekspresi bebas yang memungkinkan sebuah ide dikomunikasikan, dimodifikasi, dan disebarluaskan tanpa harus mengalami dialog secara langsung. Meme selain menjadi ekspresi humor dan satir warganet. Tulisan ini melihat perkembangan meme sebagai media komunikasi dan perkembangannya seiring wacana ekspresi humor dan kreativitas meme film pengabdi setan 2017, dengan melihat aspek implikatur dan semantic yang digunakan dalam meme Pengabdi Setan 2017 Kata kunci: meme, Ekspresi Humor, Pengabdi Setan